Optimalisasi Pengendalian Kualitas Jok Kernet dengan Peta Kendali dan 5S Menuju Zero Defect di UMKM AB - Hartono, Muhammad Ragil; Sutrisno, Sutrisno; Arifin, Jauhari; Winarno, Winarno (Fakultas Teknik Universitas Tulang Bawang, 2025)
The rapid advancement of technology in the industrial sector continues to evolve, requiring companies to remain competitive, including in the production of kernet seats. This study aims to improve the quality of kernet seat products at UMKM AB through the implementation of control charts, fishbone diagrams, and the 5S method. Based on control chart analysis, the average defect rate before improvement was 6.8 units per batch, with an upper control limit (UCL) of 12.1 and a lower control limit (LCL) of 1.46. After implementing quality control methods, the defect rate decreased to 3.2 units per batch, reflecting a 52.9% reduction. The fishbone diagram analysis identified the primary causes of defects, including suboptimal machine conditions (40%), insufficient worker skills (30%), material quality (20%), and unstandardized production methods (10%). Meanwhile, the implementation of the 5S method proved to enhance work efficiency, maintain workplace cleanliness, and optimize production time. Based on these findings, it is recommended that UMKM AB conduct regular machine maintenance, improve worker training, and carry out periodic audits on the implementation of the 5S method to ensure consistent and sustainable results. Keywords: 5S, Control, Control Chart, Quality, SMEs